The Design of Change in Waste Management Policy: Application of Soft Systems Methodology - Sari, Maria Dika Puspita; Umanto, Umanto (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
Municipality of Depok faces complex waste problems. The amount of waste continues to grow with the increasing population and people’s activities. The Local Government has established a policy to deal with the waste problems by applying the Integrated Waste Management System (SIPESAT) since 2006. However, there are some resistances in the implementation of the waste management system. This study aims to give recommendation about policy changes of waste management policy in Municipality of Depok. This research applies soft systems methodology. The use of the hierarchical policy process as proposed by Bromley (1989) indicating the role of institutions that guiding the actors at each level to perform their roles to achieve the integrated waste management system. The Local Government needs to strengthen the policy by changes the waste management policy based on the policy process that are the making of legislation on waste management at the policy level, the arrangement of SOP-UPS and optimizing the roles of Sanitary Task Force at the organizational level and the establishment of public involvement system at the operational level.